On-transit actions and outcomes of injuries from road accidents in Makueni, Kenya: the association - Anthony Wambua Mathulu; Eliab Seroney Some; Esther Marieta Ndonga (International Journal of Public Health Science (IJPHS), 2022)
Makueni County experiences a significant burden from traffic related injuries that often results to deaths and other complications. It is not clear whether the deaths and the complications are related to the actions of the responders. The purpose of this study was to provide information to enable the development of policies and programmes aimed at reducing fatality rate and life-long complications from road accidents in the Trans-African highway and other highways in Kenya. The study used the mixed method approach and applied the cross-sectional study design. Data was collected from 427 First Responders and 474 patients. Statistical tests applied included Chi-square, correlations and multinomial logistic regression. Study findings show that pre-hospital emergency care was provided to less than half (48%) of those with road traffic injuries. Study findings indicate a significant (p-value <0.05) relationship between outcome of injuries with helping with breathing, covering patients for warmth and positioning during transportation. Those transported on their side were less likely to end up with severe injury outcomes (OR 95% CI, 0.016 (0.001-0.305), 0.006). The study recommends empowerment of First Responders with appropriate First-aid equipment and skills for effective care on-transit to the health facilities.